An Intramolecular Silylene Borane Capable of Facile Activation of Small Molecules, Including Metal‐Free Dehydrogenation of Water. Issue 13 (27th February 2017) - Mo, Zhenbo; Szilvási, Tibor; Zhou, Yu‐Peng; Yao, Shenglai; Driess, Matthias
Abstract: The first single‐component N‐heterocyclic silylene borane 1 (LSi‐R‐BMes2 ; L=PhC(N t Bu)2 ; R=1, 12‐xanthendiyl spacer; Mes=2, 4, 6‐Me3 C6 H2 ), acting as a frustrated Lewis pair (FLP) in small‐molecule activation, can be synthesized in 65 % yields. Its HOMO is largely localized at the silicon(II) atom and the LUMO has mainly boron 2p character. In small‐molecule activation 1 allows access to the intramolecular silanone–borane 3 featuring a Si=O→B interaction through reaction with O2, N2 O, or CO2, and formation of silanethione borane 4 from reaction with S8 . The Si II center in 1 undergoes immediate hydrogenation if exposed to H2 at 1 atm pressure in benzene, affording the silane borane 5‐H2, L(H2 )Si‐R‐BMes2 . Remarkably, no H2 activation occurs if the single silylene LSiPh and Mes3 B intermolecularly separated are exposed to dihydrogen. Unexpectedly, the pre‐organized Si–B separation in 1 enables a metal‐free dehydrogenation of H2 O to give the silanone–borane 3 as reactive intermediate. Abstract : A single for two : The first single‐component N‐heterocyclic silylene borane activates a variety of small molecules, such as O2, N2 O, CO2, H2, and H2 O. Notably, the activation of H2 O by 1 makes it a metal‐free system for dehydrogenation of H2 O.